Skewed Pressure Characteristics of Equivalent Load in Double-Arch Tunnel - Li, Chunliu; Wang, Shuren; Wang, Yongguang; Cui, Fang; Yang, Fan (ITB Journal Publisher, LPPM ITB, 2016)
It is of great importance to reasonably estimate the surrounding rock load of a double-arch tunnel for the design, construction and stability evaluation of the tunnel. Currently, the basic theory on surrounding rock pressure of double-arch tunnels is insufficient for properly making the design and calculations. Generally, simplified calculations based on experience are used, such as the calculation method of Protodyakonovâs theory, the building code method and others. Considering the fact that the surrounding rock pressure of double-arch tunnels has skewed distribution characteristics, a computational model of a double-arch tunnel was built using data from an actual excavation of a highway tunnel. Taking some factors into consideration, such as different stress states, different construction methods and different sizes of double-arch tunnels, the pressure evolution of the surrounding rock was analyzed during step-by-step excavation of the double-arch tunnel. The results showed that in each condition the surrounding rock pressure of the double-arch tunnel displayed skewed distribution characteristics. The skewed distribution of the surrounding rock pressure varied with changes in stress state, construction sequence and excavation size. The skewed pressure of the double-arch tunnel was converted to equivalent load. The conversion method and distribution characteristics of the equivalent load are specified. They have important theoretical significance and practical value for similar engineering practices.